The Sustainable Global Marketplace 2014
DOI: 10.1007/978-3-319-10873-5_46
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Acceptance of Green Products

Abstract: The findings from this exploratory survey study (n=1300) of factors affecting the acceptance of green products indicate that consumers are more concerned with purchase risk than with product benefits. Poor product performance/failure and risk of wasting money were rated most important factors. Peer acceptance and personalization were rated least important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Indubitably, our findings revealed that EA, BE, and pricing are imperative. In electrical home appliance, pricing and BE are three of the major consideration in various studies across the countries, which include Drozdenko et al (2015) in United States, Shafiee et al (2019) in Europe, and Wickramasinghe and Mathusinghe (2016) in Sri Lanka. The willingness of consumer to pay more for green product has decline even the concern on environmental has increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indubitably, our findings revealed that EA, BE, and pricing are imperative. In electrical home appliance, pricing and BE are three of the major consideration in various studies across the countries, which include Drozdenko et al (2015) in United States, Shafiee et al (2019) in Europe, and Wickramasinghe and Mathusinghe (2016) in Sri Lanka. The willingness of consumer to pay more for green product has decline even the concern on environmental has increase.…”
Section: Discussionmentioning
confidence: 99%
“…The willingness of consumer to pay more for green product has decline even the concern on environmental has increase. Obviously, the main impediment is the personnel financial restriction especially during economic downturn ( Drozdenko et al, 2015 ). Many scholars believe that the driving force to influence CPI in green home appliance is the product branding.…”
Section: Discussionmentioning
confidence: 99%